The Effect of Interest Rates, Money Supply and Exchange Rate on Inflation in Indonesia and Libya (Business and Economic Analysis Journal, 2021)
This research purposed to analyse the effect of changes in interest rates against inflation, to analyse the effect of money supply to inflation, to analyze the effect of rupiah exchange rate on inflation. In this study the authors used a quantitative approach. This research is a secondary and quantitative data study using sample data on interest rates, the money supply and the exchange rate in Indonesia and Libya in 2005-2019. With this method the objectives to be achieved must be able to describe certain characteristics of a population. Data analysis technique used is ECM (Error Correction Mechanism) Model with EViews programs. Based on the result and analysis, the conclusion are as follows; there is no significant influence between Interest Rate on Inflation in Indonesia. In Libya, we will not use IR (Interest rate) variables because the data is not achieved the ECM criteria and cointegration. There is significant influence between Money supply on Inflation, in both Indonesia and Libya. There is no significant influence between Exchange rate on Inflation in Indonesia and Libya.